NILAI SOSIAL BUDAYA BERBASIS KARAKTER DALAM PAPPASANG TURIOLO MAKASSAR: KAJIAN SOSIOLOGI SASTRA - Hasriani Hasriani; Eka Sartika; Ratnawati Ratnawati (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
Character-Based Socio-Cultural Values in Pappasang Turiolo Makassar: Study of Sociology and Literature. This study aims to describe, explore, and explain the socio-cultural values in pappasang turiolo Makassar as a sociology study of literature. This research is a qualitative research with descriptive methods. The data in this study are in the form of words, phrases, and sentences in Papasang Turiolo Makassar. The data collection technique in this research is to study documents and literature. The results showed that the socio-cultural values of pappasang turiolo Makassar based on character were leadership values, honesty values, unity values, selfish values, and religious values. Based on the research findings, the writer hopes to contribute knowledge about culture and enrich existing research results and provide a clear picture of Pappasang Turiolo, especially the socio-cultural values contained in it, providing benefits from an explanation of Pappasang Turiolo to the community. As well as readers can take socio-cultural values which are a reflection of community life as a guide in life.